Comparative Study Between 0.125mm, 0.35mm and 0.75mmVoxel Sizes of Cone Beam Computed Tomography in Diagnosis of Secondary Caries Lesions Under Composite Restorations (An In vitro Study) - Atef Alasfar; Subhia El Shaglabow (Khalij-Libya Journal of Dental and Medical Research, 2024)
The aim of this study was to assess the diagnostic accuracy of Cone Beam Computed Tomography (CBCT) with different voxel sizes in detection of simulated recurrent caries beneath composite restoration. In this study, a total of 40 proximal slots of class II cavities were prepared on 40 extracted human premolars and molars. Then, 20 teeth were randomly selected out of these sample and artificial carious lesions were created on these teeth by a round diamond bur no .2(study group). All cavities were restored by using composites resin and radiographed with CBCT unit (Cranex 3D) using 5x5mm field of view at three voxel sizes 0.35mm, 0.125mm, 0.75mm. Intra- and inter-observer agreements were calculated with Kappa statistics (κ). The area under the receiver operating characteristic (ROC) curve was used to evaluate the diagnostic ac curacy. The AUCs value for CBCT with voxel sizes 0.35mm, 0.125mm, 0.75mm was 0.983 ,0.900,0.817, respectively. The kappa value for inter-observer agreement was 0.993,0.989,0.938; respectively. Diagnostic Accuracy of CBCT was high in detecting the simulated small secondary proximal caries under composite restoration, voxel size 0.125mm can be used to detect caries lesions with adequate accuracy and the least patient exposure dose. كان الهدف من هذه الدراسة هو تقييم الدقة التشخيصية للتصوير المقطعي المخروطي بأحجام فوكسل مختلفة في الكشف عن التسوس تحت الحشوات. في هذه الدراسة، تم تحضير ما مجموعه 40 فتحة قريبة من تجاويف الدرجة الثانية على 40 من الضواحك والأضراس البشرية المستخرجة. بعد ذلك، تم اختيار 20 سناً عشوائياً من هذه العينة وتم إنشاء آفات نخرية اصطناعية على هذه الأسنان بواسطة السن الماسي الدائري رقم 2 (مجموعة الدراسة). تم ترميم جميع التجاويف باستخدام الراتنجات المركبة وتصويرها شعاعياً بوحدة CBCT (Cranex 3D) باستخدام مجال رؤية 5 × 5 مم بثلاثة أحجام فوكسل 0.35 مم، 0.125 مم، 0.75 مم. تم حساب الاتفاقيات داخل وبين المراقبين باستخدام إحصائيات كابا (κ). تم استخدام المنطقة الواقعة أسفل منحنى خاصية تشغيل المستقبِل (ROC) لتقييم دقة التشخيص. قيمة AUCs لـ CBCT بأحجام فوكسل 0.35 مم، 0.125 مم، 0.75 مم كانت 0.983،0.900،0.817 على التوالي. كانت قيمة كابا لاتفاق بين المراقبين 0.993،0.989،0.938 على التوالي. دقة تشخيص CBCT كانت عالية في الكشف عن التسوس الثانوي تحت الترميم المركب، ويمكن استخدام حجم فوكسل 0.125 ملم للكشف عن آفات التسوس بدقة كافية وبأقل جرعة تعرض للمريض